Kajian Awal : Respon Eksplan Nodus dalam Inisiasi Tunas Mikro Tanaman Karet (Hevea brasiliensis Muell Arg.) dalam Medium MS - Permata Sari Harahap; Luthfi Aziz M. Siregar; Yusuf Husni (Jurnal Agroekoteknologi, 2015)
The aimed of the research was to determine the best medium for micro shoot induction ofrubber plant (H. brasiliensis Muell. Arg.) from node explant in MS medium. Theresearch was carried out in the In Vitro Culture Laboratory, PT. Perkebunan NusantaraIII Kebun Gunung Pamela, Tebing Tinggi, Sumatera Utara, Indonesia. The researchbegan from April to June 2014. The research used Completely Randomized Design withsixteen treatments and six replications. The results showed that combination of BAP andNAA concentrations significantly affected on percent of sterile explants and percent ofshoots emergence. Each treatment showed different result and the MS Media + 1 mg/lBAP + 0 mg/l NAA was the best media for leaf formation of the microshoot.Key words: rubber, micro shoot, BAP, NAA